2020
DOI: 10.1111/deci.12488
|View full text |Cite
|
Sign up to set email alerts
|

Why Don't You Join In? A Typology of Information System Certification Adopters

Abstract: While the importance of information system (IS) certifications to demonstrate compliance with security and personal data protection requirements is constantly increasing, competing (theoretical) viewpoints exist that outline the rationales for organizations to adopt certifications. The results of these competing perspectives are inconclusive research findings in the certification adoption literature. While organizations may use certifications to signal quality to consumers, others mainly adopt certifications t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Caballero et al (2012) found that all changes and decisions on the security and quality of personal data in health care services should be consistent with the firm's quality management system. Lins et al (2022) found that online vendors are motivated to adopt various security and privacy certifications in order to signal data protection and increase legal compliance.…”
Section: Key-component Component Descriptionmentioning
confidence: 99%
“…Caballero et al (2012) found that all changes and decisions on the security and quality of personal data in health care services should be consistent with the firm's quality management system. Lins et al (2022) found that online vendors are motivated to adopt various security and privacy certifications in order to signal data protection and increase legal compliance.…”
Section: Key-component Component Descriptionmentioning
confidence: 99%
“…As such, providing detailed arguments and evidence for why a certification authority is perceived as competent increases users' trust perceptions. In general, performing certification attestations is a complex procedure requiring a certification authority to be organized and armed with a body of knowledgeable and experienced employees (Lins et al, 2020). Certification authorities with high competence are likely to provide better assessments of system owners.…”
Section: The Impact Of Argument Quality On Certifications' Effectsmentioning
confidence: 99%
“…Information system (IS) owners have developed diverse strategies over the past years to reduce users' uncertainty and anxiety surrounding unknown or ad hoc system use. Among these strategies, certifications by third parties are the longest and most pervasively used (Lins et al, 2020;Özpolat et al, 2013). Certifications are neutral third-party attestations of specific system characteristics, operations, and management principles to prove compliance with regulatory or industry requirements (Lansing et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The receivers are the “outsiders who lack information about the organization in question but would like to receive this information” (Connelly et al., 2011). Operations management literature has examined receivers such as customers (Ba et al., 2020; Duan et al., 2021; Lins et al., 2020; Rao et al., 2018; Ray et al., 2011; Wallenburg et al., 2021), buying firms (Cheng et al., 2020; Mena et al., 2020), purchasing managers (Yan et al., 2020), and investors (Jiang et al., 2007; Kim & Wagner, 2020; Narasimhan et al., 2015). In our study, we consider investors as the receivers of the signals.…”
Section: Theory Developmentmentioning
confidence: 99%